Differential expression of a zinc finger-encoding gene in response to positive versus negative signaling through receptor immunoglobulin in murine B lymphocytes. - Seyfert, V L (1989)
Egr-1 is a murine early growth factor-inducible gene that encodes a protein with zinc fingers and that is believed to be involved in transcriptional regulation. Expression of this gene was investigated in murine B lymphocytes stimulated through their receptor for antigen (surface immunoglobulin [sIg]) with antireceptor antibodies (anti-sIg). Rapid (by 15 min) up-regulation of Egr-1 mRNA expression was observed after sIg cross-linking at a dose of anti-sIg sufficient to drive the majority of cells into cell cycle. Interestingly, signaling through sIg on the murine B-lymphoma cell line WEHI-231 did not up-regulate Egr-1 expression even though similar signaling pathways, including up-regulation of c-fos expression, are associated with this receptor in these cells. Importantly, cell growth and proliferation of WEHI-231 cells were inhibited by anti-sIg stimulation, which suggested a relationship between Egr-1 expression and differential processing of receptor immunoglobulin signals with respect to cellular growth responses. This notion was further supported by the finding that murine B lymphomas whose proliferation was not inhibited by anti-sIg showed receptor immunoglobulin-coupled Egr-1 expression. In further support of this association are results showing that under conditions in which Egr-1 expression was induced in WEHI-231 cells in response to stimulation by anti-sIg, a concomitant change was observed in the growth response of these cells. These results, then, indicate a potential role for Egr-1 expression in the translation of receptor-generated signals into cellular activation or induced unresponsiveness.